Can Owner-Manager Characteristics Signal Small Business Loan Default Propensity? - Eresia-Eke, Eresia-Eke (Journal of Economics and Behavioral Studies, 2013)
The potential of small businesses is inhibited by a cocktail of problems of which inaccessibility to finance is pre-eminent. This problem is linked to the lenders’ risk estimation, often based on financial indicators which small businesses are not adept at using to signal their performance ability. This situation, especially in South Africa, with a history of a people who were previously disadvantaged does not aid the development of small businesses that may well be the antidote for overcoming the strain of poverty and unemployment in the country. This study stems from the human capital theory and investigated possible relationships between owner-manager characteristics and loan default propensity. The aim being to unveil non-financial variables, associated with the owner-manager which could be relied upon by lenders’ to estimate the loan default propensity of the small business borrower. Primary data collected in South Africa were empirically analysed for possible associations between owner-manager characteristics and loan default propensity. Results revealed business size-dependent differences in the association between certain ownermanager characteristics and business loan default propensity. The implication of this for all stakeholders is that considerations for small business lending should be sensitive to business size.